# Answer to Question #21984 in Trigonometry for Kristen Woods

Question #21984

Simplifiy and solve

3. 30 square root of -25 * 8 sqaure root of -49

4. 6 square root of -64 + 12 square root of -36

5. 4 sqaure root of -13 - 6 square root of -13

3. 30 square root of -25 * 8 sqaure root of -49

4. 6 square root of -64 + 12 square root of -36

5. 4 sqaure root of -13 - 6 square root of -13

Expert's answer

3) 30 square root of -25 * 8 sqaure root of -49

30 * sqrt(-25) * 8 * sqrt(-49) =

= 30 * 5i * 8 *7i

= (30 * 5 * 8 *7) * (i*i)

= 8400 * (-1)

= -8400

-------------------------------------------------------

4) 6 square root of -64 + 12 square root of -36

6 * sqrt(-64) + 12 * sqrt(-36) =

= 6 * 8i + 12 *6i

= 48i + 72i

120i

-------------------------------------------------------

5) 4 square root of -13 - 6 square root of -13

4*sqrt(-13) - 6*sqrt(-13)

= -2 *sqrt(-13)

= -2 sqrt(13) *i

30 * sqrt(-25) * 8 * sqrt(-49) =

= 30 * 5i * 8 *7i

= (30 * 5 * 8 *7) * (i*i)

= 8400 * (-1)

= -8400

-------------------------------------------------------

4) 6 square root of -64 + 12 square root of -36

6 * sqrt(-64) + 12 * sqrt(-36) =

= 6 * 8i + 12 *6i

= 48i + 72i

120i

-------------------------------------------------------

5) 4 square root of -13 - 6 square root of -13

4*sqrt(-13) - 6*sqrt(-13)

= -2 *sqrt(-13)

= -2 sqrt(13) *i

## Comments

## Leave a comment